Genetic structure and diversity in Juniperus communis populations in Saxony, Germany - Reim, Stefanie; Lochschmidt, Frank; Proft, Anke; Tröber, Ute; Wolf, Heino (Biodiversity: Research and Conservation, 2016)
In recent years, land use changes led to a rapid decline and fragmentation of J. communis populations in Germany. Population isolation may lead to a restricted gene flow and, further, to negative effects on genetic variation. In this study, genetic diversity and population structure in seven fragmented J. communis populations in Saxony, Germany, were investigated using nuclear microsatellites (nSSR) and chloroplast single nucleotide polymorphism (cpSNP). In all Saxony J. communis populations, a high genetic diversity was determined but no population differentiation could be detected whatever method was applied (Bayesian cluster analysis, F-statistics, AMOVA). The same was true for three J. communis out-group samples originating from Italy, Slovakia and Norway, which also showed high genetic diversity and low genetic differences regarding other J. communis populations. Low genetic differentiation among the J. communis populations ascertained with nuclear and chloroplast markers indicated high levels of gene flow by pollen and also by seeds between the sampled locations. Low genetic differentiation may also provide an indicator of Juniper survival during the last glacial maximum (LGM) in Europe. The results of this study serve as a basis for the implementation of appropriate conservation measures in Saxony.